Discursive Placemaking Practices and White Christian Nationalism: Analyzing LGBTQIA+ Censorship Debates in a Southern, Small Town Library - Schey, Ryan; Adams, Rebekah J. (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2026)
This article examines a public library board meeting in a small Southern U.S. town with the goal of understanding local discourses about sexual and gender diversity amid increased challenges to LGBTQIA+ and BIPoC-themed books. Drawing on theories intertwining place, power, and identity, we analyze how arguments for and against censoring LGBTQIA+ materials are insidiously imbued with discursive practices part of, but not exclusive to, white Christian nationalism. Our analysis identifies three key discursive placemaking practices of white Christian nationalism that community members used: instilling fear, enforcing exclusions, and narrating temporalities (pasts, presents, and futures). Findings reveal that speakers—despite opposing ideological positions about LGBTQIA+ life—constructed a vision of their community influenced by whiteness and Christian nationalist ideologies. This analysis offers new pathways for understanding how public spaces become sites of contestation where multiple trajectories of power and identity converge, with implications for advocacy toward more inclusive and just library spaces.